Nardulli, Ed., Domestic Perspectives On Contemprorary Democracy - Sims, Rebecca (Teaching History: A Journal of Methods, 2009)
This collection of original essays concerning democracy and the challenges it faces throughout the world is the result of events beginning with the establishment of an endowed center, The Cline Center for Democracy, at the Urbana-Champaign campus of the University oflllinois. The intentional focus is on "the big picture" for democracy in the world in view of increasing diversity and "Information Age innovations." The essays originally presented at a conference in 2004 generated discussion among attending scholars representing "a variety of subdisciplines." Revisions based upon scholarly input resulted in the final collection presented here. The collection is invaluable as a tool to evaluate democracies at their various stages in the world today, to offer learned considerations and options for improving or stabilizing existing democracies and to offer best chance scenarios for establishment of lasting democracy in transition countries such as Iraq . (It is worth noting that "the companion volume, International Perspectives on Contemporary Democracy, deals with ... the prospects for a fourth wave of democratization and the challenges that globalization poses for democratic governance.")